Comparative Analysis of Secured Transport Systems Using RFID Technology for Schools (International Journal of Scientific Research in Science and Technology, 2024)
Parents place the highest priority on their children’s protection. Even with the best safety precautions, children could find themselves in a dangerous scenario (such crossing the road carelessly) since they lack the self-defense abilities to keep themselves safe. The bus unit and the school unit are the two primary components of the system. When a child boards or exits the bus, the bus unit system is used to identify their departure. The school unit receives this information, uses it to determine which kids got off the bus early, and sends out an alert message in response. To confirm that the suggested system functions as intended, a full prototype was put into practice and tested. The method appears promising for everyday transportation safety, according to the results.